Acceptability of test and treat with doxycycline against Onchocerciasis in an area of persistent transmission in Massangam Health District, Cameroon. - Rogers Nditanchou; Ruth Dixon; Kareen Atekem; Serge Akongo; Benjamin Biholong; Franklin Ayisi; Philippe Nwane; Aude Wilhelm; Sapana Basnet; Richard Selby; Samuel Wanji; Didier Bakajika; et al. (PLoS Neglected Tropical Diseases)
The main onchocerciasis elimination strategy is annual Community-Directed Treatment with ivermectin (CDTi). However, as a response to persistent high infection prevalence in Massangam Health District in Cameroon, two rounds of alternative treatments including biannual CDTi, ground larviciding and test and treat with doxycycline (TTd) were implemented. This led to a significant prevalence reduction from 35.7% to 12.3% (p<0.001) as reported by Atekem and colleagues. Here we report on the acceptability of TTd component based on qualitative and quantitative data. The TTd involved microscopic examination for microfilaria in skin biopsy and those infected were offered doxycycline 100 mg daily for 35 days by community-directed distributors (CDDs). Participation level was significantly high with 54% of eligible population (age > 8, not pregnant, not breastfeeding, not severely ill,) participating in the test in each round, increasing to 83% over the two rounds. Factors associated with non-participation included mistrust, being female; being younger than 26 years; short stay in the community; and belonging to semi-nomadic sub population due to their remote and disperse settlement, discrimination, their non selection as CDD, and language and cultural barriers. Treatment coverage was high -71% in round 1 and 83% in round 2. People moving away between testing and treatment impacted treatment coverage. Some participants noted mismatch between symptoms and test result; and that ivermectin is better than doxycycline, while others favoured doxycycline. CDD worried about work burden with unmatching compensation. Overall, TTd participation was satisfactory. But can be improved through reinforcing sensitisation, reducing time between test and treatment; combining TTd and CDTi in one outing; augmenting CDDs compensation and/or weekly visit; exploring for frequently excluded populations and adapting strategies to reach them; and use of a sensitive less invasive test.